Leveraging modern technologies in agriculture: Recent progress and prospects in Bangladesh - Md. Nahid Mahmud; Fahmida Tasnim; Ahmed Ali Omar; Yeaseen Ali (Plant Trends)
Agricultural technologies are crucial for time saving with sustainable agricultural production. However, the progress of conventional methods in agriculture, application of modern agricultural tools and their prospect of using are not well explored in perspective of Bangladesh. Therefore, updated studies on progress and prospects of modern agricultural tools in Bangladeshi agricultural sectors are highly demandable. Application of these modern agricultural tools not only improve productivity through optimizing resource usage but also help to reduce limitation of traditional farming methods. This study focuses the key areas of technological implementation of modern tools in global agricultural, current performance of those tools and their prospects of using in Bangladeshi agriculture. This review updated application of conventional agricultural tools in agricultural, comparison of traditional and modern agricultural tools using in Bangladeshi agricultural sectors, and prospect and progress of several agricultural tools in agriculture. The study discusses the current implication of precision agriculture, Internet of Things (IoT) based monitoring systems, automated irrigation, smart seed selection, and eco-friendly farming techniques. This review further explores the importance of integrating modern technologies and knowledge gaps of traditional farming, suggesting farmer centric approach supported by government policies, capacity-building initiatives, and incentives are required to ensure successful implementation of these modern tools. In this context, data-driven decision-making tools, mobile based advisory services, and renewable energy-driven systems could be useful during agricultural crop production. The extensive updated findings on importance and prospect of using modern agricultural technology opens new avenue for the agriculture policymakers, agronomists, and farmers for sustainable agricultural production in Bangladesh. [Plant Trends 2025; 3(2.000): 13-32]